WORK ENGAGEMENT IN HONORARY TEACHERS - Rasnadi, Jiemmy Eka; Safakum, Erick Fernandi Yosyanni Riezky; Musthofa, Arip; Sugiarti, Lucia Rini; Suhariadi, Fendy (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
This inquire about points to look at the components and viewpoints affecting work engagement among privileged instructors at SMPN 1 Batangan. Employing a subjective strategy with a phenomenological approach, this think about investigates the subjects' mindfulness and encounters through perception and in-depth interviews. Information investigation was conducted utilizing Bogdan and Biklen's coding strategy (Moleong, 2014). The investigate sources were three privileged instructors instructing at SMPN 1 Batangan. The comes about appear that all three witnesses experienced noteworthy work engagement issues. Source I appeared engagement issues affected by work assets (inconvenience in educating due to not coordinating their recognition and need of foundation) and individual assets (feeling belittled).